Book Review: The Oxford Handbook of Language Attrition - Zahia Flih (Journal Of Language Education and Development (JLed), 2020)
The present paper reviews The Oxford Handbook of Language Attrition edited by Monika S. Schmid and Barbara Köpke (2019). The book is the first of its kind to provide a comprehensive account of the phenomenon of language attrition. It includes numerous experts in the field offering unique insights into the topic from various perspectives (linguistic, psycho-neurolinguistic, and sociolinguistic) so as to give the reader a holistic view and understanding of exactly how the phenomenon takes place and what different factors influence its occurrence and development. The book also draws on previous studies as well as other fields to present a guideline for future research